Unveiling the rural dichotomy: the dual impact of rurality on youth mental health - Sarah Youngson; Beatriz Cuesta-Briand; Mathew Coleman (Rural and Remote Health)
Introduction: The geographic, cultural, social and economic milieu that impacts mental health in rural communities globally has been well documented. However, few studies have addressed how rural ecosystems impact specifically upon the mental health and wellbeing of young people. Furthermore, the limited explorations of factors contributing to poorer mental health outcomes in rural youth have primarily included adult voices. The study aimed to give a youth voice to the vexed problem of high rates of youth mental illness and suicide in rural and remote areas, exploring young people's experiences in a deeply contextual manner. Methods: This study followed a phenomenological qualitative design underpinned by the principles of participatory action research. A youth-led reference group provided guidance on the study design and recruitment. A total of 29 young people aged 12-19 years were recruited from a small rural community in southern Western Australia. Individual and focus group semi-structured interviews were conducted. The interviews were transcribed and subjected to thematic analysis informed by ecological systems theory. Results: The findings demonstrate the impact of a rural address on youth mental health through the influence of three overarching spheres of influence, as described by ecological systems theory: 'everyone knows everyone', 'small school and beyond' and 'the place'. Most themes included both positive and negative components, as well as ambivalence, demonstrating a double-edged sword. Conclusion: The study findings support the view that mental health in rural young people is best viewed through an ecosystem lens, acknowledging the complex and dynamic interplay between interpersonal, community and environmental factors on young people. The paradoxes and contradictions present in almost every interview are informative, instructive and of great value in considering the needs and desires of rural young people. Rural communities should be supported to build upon their intrinsic strengths to ameliorate the impact of rurality on mental health risk factors for young people. Building on the assets inherent in rural communities, could rural young people have better outcomes than urban youth?